2012
DOI: 10.1080/10916461003699184
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to the Modeling of a Simple Re-infiltration Gravity Drainage Process in Naturally Fractured Reservoirs

Abstract: One of the most important concerns regarding prediction of production performance in naturally fractured reservoirs is the issue of re-infiltration phenomena.In this study, the modeling of a simple re-infiltration process with no effect of capillary continuity between blocks is presented by extending the gravity drainage mechanism for a single block.First, a qualitative analysis of the gravity drainage process through porous media was conducted and the role of gravity and capillary forces was investigated.Then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Several authors have studied immiscible gas and MCM gas injection processes in fractured reservoirs by numerical modeling. ,, Uleberg and Høier, based on compositional reservoir modeling, showed that the developed miscibility level in a fractured reservoir is significantly higher than for a conventional one-dimensional, single-porosity system. In the numerical simulations of Suicmez et al the best results, regarding the ultimate recovery and drainage rate, were obtained for the case where miscibility develops through repeated contacts between the injected gas and the oil in the matrix (i.e., developed miscibility conditions).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have studied immiscible gas and MCM gas injection processes in fractured reservoirs by numerical modeling. ,, Uleberg and Høier, based on compositional reservoir modeling, showed that the developed miscibility level in a fractured reservoir is significantly higher than for a conventional one-dimensional, single-porosity system. In the numerical simulations of Suicmez et al the best results, regarding the ultimate recovery and drainage rate, were obtained for the case where miscibility develops through repeated contacts between the injected gas and the oil in the matrix (i.e., developed miscibility conditions).…”
Section: Introductionmentioning
confidence: 99%